Knowledge, Attitude, Practice, Perception, and Psychological Response of Nurses Regarding Covid-19; Literature Review - Ramla Wati; Kusrini Kadar; Takdir Tahir (Universitas Aisyah Pringsewu, 2021)
COVID-19 is a disease caused by a new corona virus resembling pneumonia and first appeared in China's Wuhan Province in November 2019. Nurses play an important role in health care settings, including prevention, infection control, isolation, continuous patient monitoring, and have occupational risk as well as high risk of exposure in providing care during the COVID-19 outbreak. The purpose of this literature review is to identify nurses' knowledge, attitudes, practices, perceptions, and psychological responses to COVID-19. This research method is a literature review. Search for articles using six databases namely PubMed, Ebscohost, Chocrane Library, ClinicalKey for Nursing, Science Direct, and Gray Literature using keywords based on PICO. There are 1,149 articles identified from 2019-2021, was found 21 relevant articles that were discussed and analyzed. Results: The majority of nurses had a good level of knowledge, had positive attitudes, good practices, and positive perceptions of COVID-19. Nurses are experiencing stress and psychological responses during the COVID-19 pandemic. Conclusion: The majority of nurses have a good level of knowledge, but there are still nurses who have less knowledge about diagnosis, prevention, treatment and control of COVID-19 infection, besides that nurses also experience psychological responses such as anxiety and depression related to COVID-19.